2021
DOI: 10.7150/ijbs.62571
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated fibroblasts-derived exosomal miR-3656 promotes the development and progression of esophageal squamous cell carcinoma via the ACAP2/PI3K-AKT signaling pathway

Abstract: Esophageal squamous cell carcinoma (ESCC) is one of the most common gastrointestinal tumors, accounting for almost half a million deaths per year. Cancer-associated fibroblasts (CAFs) are the major constituent of the tumor microenvironment (TME) and dramatically impact ESCC progression. Recent evidence suggests that exosomes derived from CAFs are able to transmit regulating signals and promote ESCC development. In this study, we compared different the component ratios of miRNAs in exosomes secreted by CAFs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…In our previous study, we found that FGFR2 (FGFR2 mentioned in our study is FGFR2-IIIc) was a speci c surface marker of CAFs in esophageal squamous cell carcinoma (ESCC) (10). We have demonstrated that FGFR2 + CAFs actively interacted with ESCC cells through secreting multiple factors to support tumorigenesis and promote metastasis (11)(12)(13)(14). However, their precise origin and mechanisms about their recruitment and maturation are completely unknown.…”
Section: Introductionmentioning
confidence: 80%
“…In our previous study, we found that FGFR2 (FGFR2 mentioned in our study is FGFR2-IIIc) was a speci c surface marker of CAFs in esophageal squamous cell carcinoma (ESCC) (10). We have demonstrated that FGFR2 + CAFs actively interacted with ESCC cells through secreting multiple factors to support tumorigenesis and promote metastasis (11)(12)(13)(14). However, their precise origin and mechanisms about their recruitment and maturation are completely unknown.…”
Section: Introductionmentioning
confidence: 80%
“… 4 , 5 It was reported that CAFs-derived exosomes could affect cell proliferation, migration and invasion of cancer cells. 6 , 7 CAFs-derived exosomes enhanced drug resistance in CRC through priming cancer stem cells. 8 LncRNAs, miRNAs and circular RNAs (circRNAs) participate in the crosstalks between CAFs and cancer cells, thereby accelerating tumor progression, which are enriched in exosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular vesicles (EVs) are extracellular membrane particles’ component with diameters of 40–1,000 nm, whose outer layer is a bilayer lipid membrane while the inside encapsulates different proportions of DNA, RNA, and protein components ( Jin et al, 2021 ). Numerous reports indicate that EVs are usually existing in body fluids, including cerebrospinal fluid, blood, urine, saliva, pleural effusion, and ascites ( Caivano et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%